An epidemic model for security and performance of wireless sensor networks. (17th May 2019) - Ojha, Rudra Pratap; Sharma, Kavita; Srivastava, Pramod Kumar; Sanyal, Goutam
Wireless sensor networks have imminent constraints that make security a crucial issue. Transmission starts from a single node and spread in the entire network through wireless communication. This process leads to the failure of whole wireless sensor network. In the proposed mathematical model based on epidemic theory, the different class of nodes was considered to examine its effect on the network and to develop a control mechanism to prevent worm transmission in the sensor networks. It also discussed the role of communication radius on the stability of network. We examine the proposed model using stability theory of differential equation. We determine the basic reproduction number and relate with communication radius. We analyse the proposed model that improves the efficiency of the network in terms of stability and energy efficiency. We validate the proposed model through extensive simulation results.